Dictionary of Arabic Loanwords in the Languages of Central and East Africa - Baldi, Sergio, (Handbook of Oriental Studies. Section 1 The Near and Middle East ;, 2021)
"Following the publication in 2008 of Dictionnaire des emprunts arabes dans les langues de l'Afrique de l'Ouest et en Swahili, Dictionary of Arabic Loanwords in the Languages of Central and East Africa completes and offers the results of over 20 years of research on Arabic loanwords. The volume reveals the impact Arabic has had on African languages far beyond the area of its direct influence. As in the previous volume, the author analyses the loans in the greatest possible number of languages spoken in the area, based on the publications he found in the most important libraries of the main universities and academic institutions specialised in the field. By suggesting the most frequently used Arabic loanwords, the dictionary will be an invaluable guide to African-language lexicon compilers, amongst others"--